2003
DOI: 10.1101/gad.1090803
|View full text |Cite
|
Sign up to set email alerts
|

Cop9/signalosome subunits and Pcu4 regulate ribonucleotide reductase by both checkpoint-dependent and -independent mechanisms

Abstract: The signalosome is implicated in regulating cullin-dependent ubiquitin ligases. We find that two signalosome subunits, Csn1 and Csn2, are required to regulate ribonucleotide reductase (RNR) through the degradation of a small protein, Spd1, that acts to anchor the small RNR subunit in the nucleus. Spd1 destruction correlates with the nuclear export of the small RNR subunit, which, in turn, correlates with a requirement for RNR in replication and repair. Spd1 degradation is promoted by two separate CSN-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
250
0
10

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(270 citation statements)
references
References 55 publications
10
250
0
10
Order By: Relevance
“…However, UV treatment was found to cause the association between phosphorylated RNA polymerase II and the CSA-DDB1-CUL4A-ROC1/Rbx1-CSN complex. Consistent with these observations, a complex containing spCUL4/Pcu4, DDB1 homologue Ddb1 and CSN was isolated in fission yeast (Liu et al, 2003).…”
Section: Cullinssupporting
confidence: 64%
“…However, UV treatment was found to cause the association between phosphorylated RNA polymerase II and the CSA-DDB1-CUL4A-ROC1/Rbx1-CSN complex. Consistent with these observations, a complex containing spCUL4/Pcu4, DDB1 homologue Ddb1 and CSN was isolated in fission yeast (Liu et al, 2003).…”
Section: Cullinssupporting
confidence: 64%
“…However, this cannot exclude the possibility that small amount of CSN1 disassociated from or unassociated with the complex may exist transiently under certain conditions. The finding that CSN1 and CSN2 can function independently of other CSNs in fission yeast is consistent with this speculation (Mundt et al, 1999;Liu et al, 2003). By native gel electrophoresis, Fukumoto et al, (2005) showed that CSN complexes are more dynamic and heterogeneous than previously believed.…”
Section: Discussionsupporting
confidence: 77%
“…S. cerevisiae Dif1 or Schizosaccharomyces pombe Spd1 retain Rnr2 in the nucleus, preventing its interaction with cytoplasmic Rnr1. Like Crt1 or Sml1, deletion of spd1 or dif1 increases RNR activity and suppresses the lethality of checkpoint mutants (Liu et al 2003;Lee et al 2008;Wu and Huang 2008). Even though no clear orthologs for yeast RNR inhibitory proteins have been found in mammals, evidence suggests that the connection between ATR and RNR is conserved to some extent.…”
mentioning
confidence: 99%
“…S. cerevisiae Dif1 or Schizosaccharomyces pombe Spd1 retain Rnr2 in the nucleus, preventing its interaction with cytoplasmic Rnr1. Like Crt1 or Sml1, deletion of spd1 or dif1 increases RNR activity and suppresses the lethality of checkpoint mutants (Liu et al 2003;Lee et al 2008;Wu and Huang 2008 (Bester et al 2011;Danilova et al 2014). Furthermore, CHK1 activation by topoisomerase inhibitors induces the expression of RRM2 through E2F-dependent transcription (Zhang et al 2009).…”
mentioning
confidence: 99%